The Effect of High Intensity Intermittent Exercise on Power Output for the Upper Body - Leonie Harvey; Matthew Bousson; Chris McLellan; Dale I. Lovell (MDPI AG, 2015)
The aim of the present study was to examine and measure high intensity, intermittent upper body performance, in addition to identifying areas of the body that affect the variance in total work done during the 5 × 6 s sprint test. Fifteen males completed an upper body 5 × 6 s sprint test on a modified electro-magnetically braked cycle ergometer, which consisted of five maximal effort sprints, each 6 s in duration, separated by 24 s of passive recovery. A fly wheel braking force corresponding to 5% of the participants' body weight was used as the implemented resistance level. Body composition was measured using dual-energy X-ray absorptiometry (DEXA). Percent (%) decrement was calculated as 100 − (Total work/ideal work) × 100. Significant (P < 0.05) differences were found between sprints for both absolute and relative (W, W·kg−1, W·kg−1 Lean body mass (LBM) and W·kg−1 Upper body lean body mass (UBLBM)) peak (PP) and mean (MP) power. The % decrement in total work done over the five sprints was 11.4%. Stepwise multiple linear regression analysis revealed that UBLBM accounts for 87% of the variance in total work done during the upper body 5 × 6 s sprint test. These results provide a descriptive analysis of upper body, high intensity intermittent exercise, demonstrating that PP and MP output decreased significantly during the upper body 5 × 6 s sprint test.